The Effect of Problem-Based Learning Models on Students’ Mathematical Problem-Solving Ability: A Meta-Analysis - Salsabila, Shafa; Asih, Endang Cahya Mulyaning (Jurnal Pendidikan MIPA, 2024)
This study aims to analyze the significant influence of the Problem-Based Learning (PBL) model on students' mathematical problem-solving abilities. This meta-analysis includes ten scientific articles comparing the PBL model with conventional teaching methods. The article selection process followed the PRISMA 2020 guidelines to ensure transparency and rigor. Data were analyzed using the Mann-Whitney U test due to the non-normal distribution, and Spearman’s Rank Correlation was used to assess the strength of the relationship between PBL and students' problem-solving abilities. The results indicate that the PBL model has a significant and positive impact on students' mathematical problem-solving abilities compared to conventional methods, with a large effect size of r = 0.642. The Spearman’s Rank Correlation revealed a strong positive relationship (r_s = 0.782) between the implementation of PBL and the improvement in problem-solving skills. These findings are supported by several factors contributing to PBL's success, including active student engagement, effective teacher facilitation, the use of real-world contexts, and a supportive classroom environment. This study concludes that the PBL model is a highly effective pedagogical approach for enhancing mathematical problem-solving skills. Considering the significant positive effects, this study recommends the widespread adoption of PBL in educational environments to improve students' critical thinking and problem-solving abilities. Further research is needed to explore the long-term impacts of PBL and its application in different educational contexts.         Keywords: problem-based learning, mathematical problem-solving, meta-analysis, mann-whitney u test, spearman’s rank correlation. DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp864-877